Numerical Definition of Drainage Network and River Basin Area in Digital Elevation Model for Hydrological Modelling - Sulianto, A. Adi; Sutan Haji, A. Tunggul (Fakultas Teknologi Pertanian Universitas Brawijaya, 2006)
A set of computer program and algorithm for an automatic determination of drainage network and River Basin Area (RBA) by means of a Digital Elevation Model (DEM) is Â presented. The algorithms execute such tasks as DEM aggregation, identify and treatment of depression, increase of flat area relief; determination of current direction; determination of boundary of RBA and Sub-RBA, determination of River Basin Upstream Area and evaluation of drainage network composition. A computer program was made using a software, known as the Visual Basic.Â The aims of the development of the computer program and algoritms were to quickly determine the properties value of current direction drainage network and Sub-RBA based on the available DEM which may be further used in the development of water run-off models, RBA discrete, or used for statistical analysis as well as to evaluate the topology of drainage network. Result obtained from DEM evaluation were then selected and presented. Such an approach may be applicable for studying hydrology and geomorphology. Â Key Words: drainage network, river basin area, digital elevation model